Evaluación de técnicas de manejo y conservación post-cosecha para consumo fresco y procesado de chirimoya (Annona cherimola Mill.), procedentes de fenotipos nativos de la provincia de Loja - Jaramillo García, Luis Fernando (2024)
Previous researches have tried to find by either chemical, biological or traditional techniques the way to increase the post-harvest life of cherimoya, but, their scope or potential has not been achieved in this fruit. Thus, the necessity to identify post-harvest handling and conservation techniques for fresh and processed consumption of cherimoya (Anona cherimola Mill), from native phenotypes present in the Calvas, Gonzanama and Loja cantons, arose. For the conservation of the fruit, 6 treatments were carried out combining vacuum sealing with different temperatures and different places of origin. To preserve the pulp, 12 treatments were used, combining antioxidants and different temperatures. Using vacuum fruit preservation, an effective preservation of weight, diameter, soluble solids, firmness and titratable acidity was found, and this was enhanced with a decrease in temperature. It was also observed that the colors of the exocarp and pulp were better. With respect to the pulp, better preservation of soluble solids was verified by applying sodium erythrobate and potassium sulfite combined with refrigeration. Using descriptors for cherimoya obtained from International & CHERLA (2008), preservation was evaluated considering flavor, texture, fiber content and pulp oxidation. Qualitatively, it was identified that both sodium erythrobate and potassium sulfite at 4°C and -18°C (refrigeration) present better preservation.